A strategic management paper for First Women's Credit Corporation (FWC) - Alaras, Adora Teresa A. (Animo Repository, 1997)
Lending investors is an existing but largely overlooked market of the Philippine financial system. They are not regulated and their operations are not monitored, thus lending investors continue to proliferate. Despite their growing number they do not pose a big threat to each other since they are mostly small and operate at the grassroots level. The entry of First Women Credit Corporation (FWC) revolutionized the segment, so it was not surprising that it emerged on top of the industry. FWC has been in operation since 1992, with a huge network of branches and offices, as well as personnel, it focused its efforts in luring working middle class women to avail of loans from them fast and easy, albeit, at a high interest rate. However, revenues from the high interest rates it charges largely go to its debt servicing. FWC in effect borrows money and lends it out to the consumers, making profit from the interest rate differentials. The paper suggests that FWC divest itself of the assets which it acquired through the merging of FWC and U-J-P Metals. This will enable FWC to focus and concentrate on its financial services business and to have additional working capital to beef up its position at the top of the lending investors segment. Though the amount may not be substantial it will do much in putting FWC in a better financial position to undertake future expansions. A business aspect which FWC should also be considered is its initially identification as a lending institution catering to women. The paper further recommends that the thrust be altered to enable FWC to lend out to people regardless of sex, since the need for funds by both male or female is no different. Furthermore, the change in marketing strategy from differentiated to undifferentiated will double the market opportunities for FWC which will enable it to have a bigger share of the pie and maintain its leadership. In addition, the paper advise that FWC look into the future by addressing the opportunities and threats inherent to the industry such as the business opportunities that the Free Trade will bring to the country, the focus on exports as well as the OCW market that they need to tap.